2023
DOI: 10.3390/f14071400
|View full text |Cite
|
Sign up to set email alerts
|

Do All Types of Restorative Environments in the Urban Park Provide the Same Level of Benefits for Young Adults? A Field Experiment in Nanjing, China

Abstract: Previous research has consistently shown that exposure to natural environments provides a variety of health benefits. The purpose of this study is to investigate the restorative benefits of non-virtual environments in field experiments as well as the differences in physiological and psychological effects between different types of restorative sites for stressed young adults. This controlled study design used the Positive and Negative Affect Schedule (PANAS), electroencephalogram (EEG), and heart rate variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…At 18 Hz, beta waves can be subdivided into β1 (low frequency: 13-18 Hz) and β2 (high frequency: 18-30 Hz), where β1 waves represent a relaxed, focused, and coordinated mental state, and β2 waves represent an alert and excited state of tension [48]. Studies have used EEG to analyse the beneficial effects of blue spaces on mental health [4], to examine perceived fear in different types of nocturnal environments [49], and to confirm the restorative effects of various types of immersion in nature on youths experiencing stress [1].…”
Section: Objective and Reliable Measurement Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 18 Hz, beta waves can be subdivided into β1 (low frequency: 13-18 Hz) and β2 (high frequency: 18-30 Hz), where β1 waves represent a relaxed, focused, and coordinated mental state, and β2 waves represent an alert and excited state of tension [48]. Studies have used EEG to analyse the beneficial effects of blue spaces on mental health [4], to examine perceived fear in different types of nocturnal environments [49], and to confirm the restorative effects of various types of immersion in nature on youths experiencing stress [1].…”
Section: Objective and Reliable Measurement Toolsmentioning
confidence: 99%
“…Rapid and intensive urbanization on a globally scale not only leads to a monotonous, fast-paced lifestyle but also exacerbates the degradation of natural and human habitats, adversely affecting public health [1,2]. Numerous studies have indicated that exposure to natural environments, such as urban green spaces [3] and blue spaces [4], can reduce stress [5,6], increase happiness [7] and improve attention recovery [8], thereby offering psychological restorative benefits.…”
Section: Introductionmentioning
confidence: 99%
“…At 18 Hz, beta waves can be subdivided into β1 (low frequency: 13-18 Hz) and β2 (high frequency: 18-30 Hz), where β1 waves represent a relaxed, focused, and coordinated mental state and β2 waves represent an alert and excited state of tension [51]. Studies have used EEG to analyze the beneficial effects of blue spaces on mental health [6] to examine perceived fear in different types of nocturnal environments [52] and to confirm the restorative effects of various types of immersion in nature on youths experiencing stress [1].…”
Section: Objective Subjective and Reliable Measurement Toolsmentioning
confidence: 99%
“…Rapid and intensive urbanization on a global scale not only leads to a monotonous, fast-paced lifestyle but also exacerbates human disconnection from nature and the fragmentation of rural ecological landscapes [1,2]. With increasing global attention to ecological, environmental protection and carbon neutrality issues, scholars have started researching the features and characteristics of rural settlement landscapes from perspectives such as landscape genetics, ecological environment, and landscape aesthetics, emphasizing the importance of restoring rural natural landscapes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, contributes to the enhancement of the positive impact of riverside spaces on emotions and the reinforcement of public health promotion through everyday landscapes in densely populated cities. The advent of portable wearable sensors has made it feasible to capture the counter experience of natural environments [45]. It can be seen that by collecting the emotional perceptions of individuals in constructed riverside spaces, a more comprehensive and objective evaluation of environmental influence can be achieved, thereby facilitating a more appropriate assessment of spatial design.…”
Section: Introductionmentioning
confidence: 99%